Myasthenia gravis, Castleman disease, pemphigus, and anti-phospholipid syndrome - Jakubíková, Michala; Piťha, Jiří; Latta, Jan; Ehler, Edvard; Schutzner, Jan (Muscle & nerve, 2013)
INTRODUCTION: Myasthenia gravis is an autoimmune disease marked by neuromuscular transmission failure at the neuromuscular junction. Castleman disease is a rare lymphoproliferative disease characterized by non-cancerous angiofolicular hyperplasia of lymphatic tissue. METHODS AND RESULTS: We describe a young man with rapid, successive manifestations of myasthenia gravis, a solitary form of Castleman disease, pemphigus vulgaris, and anti-phospholipid syndrome, which resulted in 2 ischemic cerebrovascular events that caused a severe central neurological deficit. DISCUSSION: We were unable to find a similar case in the literature, but we hypothesize that the temporal concidence of these clinical entities may be related to a common immunological pathway, such as B-cell activation. Therefore, we treated the patient with an immunosuppressant and anticoagulant treatment, as well as rituximab, a monoclonal antibody therapy against CD20+.
Keywords: Neurologic Examination; dospělí; cévní mozková příhoda; Tomography, X-Ray Computed; Humans; nádory břicha; Pemphigus; blefaroptóza; myasthenia gravis; Fatal Outcome; antifosfolipidový syndrom; Blepharoptosis; svalová slabost; hyperplazie velkých lymfatických uzlin; fatální výsledek; mužské pohlaví; Stroke; Abdominal Neoplasms; diplopie; Adult; neurologické vyšetření; Muscle Weakness; Myasthenia Gravis; Castleman Disease; lidé; pemfigus; počítačová rentgenová tomografie; Diplopia; Antiphospholipid Syndrome; Male